Predictors of Irish 11 to 12-year-olds' road use behaviour and investigation of associated parental risk perception of own and Child's behaviour - Martin, Maggie (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
This study sought to gain a better insight into the road use behaviour of Irish primary school children aged between 11 and 12 years in Ireland.To do so required an assessment of their reported road use behaviour, their road safety beliefs and their perception of risk. This was followed for completeness by an assessment on how that relates to their parents¿ perception of risk and parents¿ perception of their child¿s own road use behaviour. This large-scale research was carried out over two waves. The first study involved the analysis of self-reported road use behaviour in 1,100 children aged 11 to 12 years in 42 Irish primary schools. Statistical modelling with HLM was employed to control for nested data within the school structure. The second study assessed the self-reported behaviour and road risk perception in 125 child and parent dyads. Overall, this research confirmed the psychometric properties of the Adolescent Road Users Questionnaire (ARBQ; Elliott & Baughan, 2004) in Ireland producing a 20-item scale appropriate for use in the 11- to 12-year-old primary school population. This scale can be used to assess changes in primary school children¿s road use behaviour over time in Ireland. Consistent across each of the behaviours assessed was that living in an urban area has a significant impact in the higher levels of unsafe crossing and dangerous play with lower levels of planned protective behaviour, possibly due to the impact of greater frequency of being out around the roads either on their own or with friends. The predictors of children and their parents¿ perception of road safety risk identified key factors which can increase or decrease the perception of child pedestrian risk. It further highlighted the relationship between how parents believe their children behave while on the roads and how their children actually behave. It suggested that parents are not fully aware of their children¿s behaviour and at times appeared to be overestimating their abilities. These two studies when compared demonstrated strong consistencies between the importance of responsibility beliefs, the impact of parental and peer modelling, the need for both parents and children to be aware of near miss events and how to avoid them in the future to close the gap between how children are behaving and how their parents perceive them as behaving.
APPROVED
Keywords: Adolescent Road User Behaviour Questionnaire; Self reported adolescent pedestrian behaviour; Parental modelling pedestrian behaviour; Theory of Planned Behaviour Pedestrian; Adolescent road use behaviour; Parental perception of pedestrian risk; Child pedestrian risk; Young adolescent predictor pedestrian risk